The zinc-binding domain of Nna1 is required to prevent retinal photoreceptor loss and cerebellar ataxia in Purkinje cell degeneration (pcd) mice - Chakrabarti, Lisa (2008)
The Purkinje cell degeneration (pcd) mouse undergoes retinal photoreceptor degeneration and Purkinje cell loss. Nna1 is postulated to be the causal gene for pcd. We show that a BAC containing the Nna1 gene rescues retinal photoreceptor loss and Purkinje cell degeneration, confirming that Nna1 loss-of-function is responsible for these phenotypes. Mutation of the zinc-binding domain within the transgene destroyed its ability to rescue neuronal loss in pcd(5J) homozygous mice. In conclusion, Nna1 is required for survival of retinal photoreceptors and other neuron populations that degenerate in pcd mice. A functional zinc-binding domain is crucial for Nna1 to support neuron survival.